Striving to establish a care relationship-Mission possible or impossible?-Triad encounters between patients, relatives and nurses - Anette Johnsson; Petra Wagman; Åse Boman; Sandra Pennbrant (Wiley, 2019)
Abstract Background When patients, relatives and nurses meet, they form a triad that can ensure a good care relationship. However, hospital environments are often stressful and limited time can negatively affect the care relationship, thus decreasing patient satisfaction. Objective To explain the care relationship in triad encounters between patients, relatives and nurses at a department of medicine for older people. Design A qualitative explorative study with an ethnographic approach guided by a sociocultural perspective. Method Participatory observations and informal field conversations with patients, relatives and nurses were carried out from October 2015‐September 2016 and analysed together with field notes using ethnographic analysis. Result The result identifies a process where patients, relatives and nurses use different strategies for navigating before, during and after a triad encounter. The process is based on the following categories: orienting in time and space, contributing to a care relationship and forming a new point of view. Conclusion The result indicates that nurses, who are aware of the process and understand how to navigate between the different perspectives in triad encounters, can acknowledge both the patient's and relatives' stories, thus facilitating their ability to understand the information provided, ensure a quality care relationship and strengthen the patient's position in the health‐care setting, therefore making the mission to establish a care relationship possible.